Toplumsal Regresyon Sırasında Kolektif Kimlik: Kendini Tanımlamadan İnsan Dışı Özellik İlişkilendirmelerine Dönüşüm - Oksuzoglu, Gizem (Bursa Teknik Üniversitesi, 2024)
In this study, collective identity is explored in relation to socio-political discourses within a historical context through the 13th regression element, which is an association of others with subhuman traits. Arguments are supported through longitudinal documentary analysis and secondary data from unstructured interviews. Discourse analysis was used to analyse data. This article presents several symbolisms relevant to emerging collective identity discourses and provides evidence of how socio-political changes throughout history can cause a change or confusion in collective identity. It also argues that societies with prolonged ethnic conflict, which are under the profound influence of a mainland, are very likely to have dual identities and dissimilar identifications among their group members. Through its analysis, this article develops Volkan’s Tree Model and suggests a phase IV in light of the existing dynamics in Cyprus. This study suggests the inclusion of all possible stages in co-existence, from dissociation to unification, in proposed phase IV.

In this study, collective identity is explored in relation to socio-political discourses within a historical context through the 13th regression element, which is an association of others with subhuman traits. Arguments are supported through longitudinal documentary analysis and secondary data from unstructured interviews. Discourse analysis was used to analyse data. This article presents several symbolisms relevant to emerging collective identity discourses and provides evidence of how socio-political changes throughout history can cause a change or confusion in collective identity. It also argues that societies with prolonged ethnic conflict, which are under the profound influence of a mainland, are very likely to have dual identities and dissimilar identifications among their group members. Through its analysis, this article develops Volkan’s Tree Model and suggests a phase IV in light of the existing dynamics in Cyprus. This study suggests the inclusion of all possible stages in co-existence, from dissociation to unification, in proposed phase IV.
Collective Identity During Societal Regression: Transformation from Self-Identification to Sub-Human Trait Associations
Keywords: Political Sociology; Siyaset Sosyolojisi